EVALUASI PROGRAM PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) BAGI TENAGA PENDIDIK DI LINGKUP DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN TAKALAR - Agustin; Irmawati; Sri Hastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the Continuing Professional Development (CPD) Program for educators within the Department of Education and Culture of Takalar Regency, as well as its supporting and inhibiting factors in the Department of Education and Culture of Takalar Regency. This study uses a qualitative approach with descriptive research methods. Data collection was carried out through observation, interviews, and documentation, with research subjects being the head of the department, division heads, and teachers. Data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing, while data validity was tested using source and method triangulation. The results show that in terms of context, CPD aligns with the regional education conditions and serves as an important strategy to improve teachers' competence in pedagogy, professionalism, and the use of digital technology. In terms of input, CPD has an adequate operational foundation with competent facilitators. proportional budget, as well as curriculum-based materials using the latest curriculum through SIMPKB data verification. In terms of process, the implementation runs systematically with a clear schedule, varied methods, and activities such as IKM technical guidance, digitalization training, and literacy workshops, although teacher motivation and readiness still vary. In terms of product, PKB has a positive impact on improving teachers' pedagogical and professional competence, reflected in participation in SIMPKB, PPG, and changes to more interactive teaching behavior. Supporting factors include policies from the education office, facilitators, study groups, and school support, while obstacles include limited access for honorary teachers, administrative requirements for new teachers, varying motivation, and difficulties in technology mastery for senior teachers.